Helping men to quit smoking - Md Aris, Mohd Aznan (2020)
Smoking accounts for one in every five death in Malaysia • About 20,000 Malaysian die each year as a result of smoking. • These number will be increase to 30,000 by the year 2030. • Today , there are about five million or 22.8 % smokers (aged 15 year old and above) in Malaysia, each consumption an average of 14 cigarettes per day.(NHMS 2016) • 4 out 10 or 7.6 million adults are exposed to secondhand smoke inside their houses, 4 of 10 or 2.3 million adults at workplaces, and 7 out 10 or 8.6 million adults at public places like restaurants. • 600,000 people die every year from exposure to secondhand or passive smoking.(WHO)